Reimagining Internships in the Digital Age: Virtual Communication Practices for Smarter Student Engagement - Indri Alya Himawan; Siti Maharani Nadira; Nabila Fenelia (Ilomata International Journal of Social Science, 2026)
This study examines the influence of communication practices on internship experiences in virtual, physical, and hybrid formats. The study employed a qualitative interpretive design, utilizing three focus group discussions comprising 15 final-year communication students at Sunway University, with five participants in each modality group. Reflexive thematic analysis was used to look at the discussions and find patterns in how students felt about onboarding, mentoring, feedback, social presence, and work-related fatigue. The results indicate that virtual internships were frequently perceived as adaptable and effective for task coordination; however, participants also reported delayed clarification, diminished spontaneous interaction, and limited opportunities for informal learning and networking. People generally thought that physical internships offered more interpersonal cues, faster feedback, and better day-to-day support for relationships. However, the quality of mentoring still varied from supervisor to supervisor. Some people said that hybrid internships offered a partial balance between flexibility and access to relationships, but how well they worked depended on how communication was set up in both online and in-person settings. The findings do not imply that one modality is inherently superior. Due to being an exploratory study with a small, context-specific sample, these findings should be regarded as interpretive insights rather than universally applicable conclusions.